2018
DOI: 10.1177/0956797617739704
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent and Under Which Circumstances Are Growth Mind-Sets Important to Academic Achievement? Two Meta-Analyses

Abstract: Mind-sets (aka implicit theories) are beliefs about the nature of human attributes (e.g., intelligence). The theory holds that individuals with growth mind-sets (beliefs that attributes are malleable with effort) enjoy many positive outcomes-including higher academic achievement-while their peers who have fixed mind-sets experience negative outcomes. Given this relationship, interventions designed to increase students' growth mind-sets-thereby increasing their academic achievement-have been implemented in scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

62
676
12
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 697 publications
(769 citation statements)
references
References 39 publications
62
676
12
19
Order By: Relevance
“…Thus, mindfulness is not a fixed trait, but rather a malleable characteristic that can be fostered by education. The evidence is less clear that other social–emotional characteristics (e.g., grit and growth mindset) can be altered in such a direct and actionable manner, especially for adolescents (e.g., (Orosz, Peter‐Szarka, Bothe, Toth‐Kiraly, & Berger, ; Sisk, Burgoyne, Sun, Butler, & Macnamara, ). Our findings encourage further development of school‐based MBIs that foster mindfulness because greater mindfulness relates to better academic outcomes for diverse middle school students.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mindfulness is not a fixed trait, but rather a malleable characteristic that can be fostered by education. The evidence is less clear that other social–emotional characteristics (e.g., grit and growth mindset) can be altered in such a direct and actionable manner, especially for adolescents (e.g., (Orosz, Peter‐Szarka, Bothe, Toth‐Kiraly, & Berger, ; Sisk, Burgoyne, Sun, Butler, & Macnamara, ). Our findings encourage further development of school‐based MBIs that foster mindfulness because greater mindfulness relates to better academic outcomes for diverse middle school students.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent meta-analytic work suggests the relationship is more complicated. A recent meta-analysis (Sisk, Burgoyne, Sun, Butler, & Macnamara, 2018) of the relationship between mindset and achievement found only a small correlation between the two (r = .1) and a small effect (d = .08) of growth mindset interventions, and only for at-risk and lower SES students. Mindset interventions were non-significant for adolescents and regular students.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that TOI influences self-regulatory behavior, such as goal-orientation and helpless versus mastery-oriented strategies, and academic achievement (Burnette et al, 2013). In parallel, mindset interventions have been developed to stimulate a growth mindset in high school students and thereby increase motivation for learning, resilience to setbacks, and educational achievement, with varying success (Sisk, Burgoyne, Sun, Butler, & Macnamara, 2018). Experience-dependent plasticity can be seen as a neurobiological basis for the growth mindset.…”
Section: Nature Of the Intervention And Its Challenges As Anticipatedmentioning
confidence: 99%